A complete mitochondrial DNA genome of whitefly species (Hemiptera: Aleyrodidae) from Litchi chinensis. Issue 2 (3rd July 2019) - Wang, Hua-Ling; Lei, Teng; Liu, Yin-Quan
Abstract: A novel complete mitochondrial genome (mitogenome) of whitefly species, collected from Litchi chinensis at Fujian province of China (hereafter whitefly_ Litchi chinensis _China) (GenBank accession number: MH999477), was described in this study. The mitogenome of whitefly_ Litchi chinensis _China is 15, 360 bp in length and contains 13 protein-coding genes, 21 transfer RNAs, 2 ribosomal RNAs and a non-coding AT-rich region (D-loop). The arrangement of mitochondrial genes of whitefly_ Litchi chinensis _China are identical with Aleurochiton aceris, but remarkably different from the mitogenomes of the other whitefly genus. Most protein-coding genes (PCGs) start with ATN, except for nad2, cox2 and atp6 genes starting with TTG, GTG, and TTG, respectively; 10 of the 13 PCGs use the typical stop codon TAN, whereas cox1, and cox2 stop with a single T. Phylogenetic analyses based on 13 PCGs support the close relationship of the sample with Aleurochiton aceris, which would provide us further insights on the taxonomy and phylogeny of Aleyrodidae.